Perbedaan Forgiveness pada Lansia yang Tinggal di Panti Wredha dan di Rumah - Lumadyo, Davin Aristyo Rahadiyan; Sandjaja, Stefanus Soejanto (Noetic Psychology, 2013)
Abstract. This research aimed to determine whether there is a difference between forgiveness of the elders who live in nursing home and in home. This study used a quantitative methods approach and used t-test statistic technique. The forgiveness were measured by TRIM 18 scale. The subjects were elderly aged 65 years old or above with random sampling (n=89). The result showed that there are differences between forgiveness the elders who live in nursing home and in home. Elders who live in nursing home have a fair score in forgiveness category and elders who live in home have a low score in forgiveness category. The result of data analysis showed the value of t is 3.440 with probability (p) < 0.05. If viewed from the mean value, there is a significant difference, in which the highest value of mean obtained by the elders who live in nursing home = 43.75 and the elders who live in home = 36.14.ÃÂ Keywords: elderly, forgiveness, nursing homeÃÂ